Information System for Macroprudential Policies - Dragomir-Constantin, Florentina-Loredana (Acta Universitatis Danubius. Œconomica, 2025)
A macroprudential system is crucial for national security as it ensures financial stability and prevents crises that could negatively impact both the economy and state security. By identifying and managing systemic risks, it protects critical institutions from economic shocks and prevents the spread of financial instability. Strengthening resilience against external threats, including cyberattacks and geopolitical fluctuations, ensures the continuity of financial infrastructures essential for economic stability. Macroprudential policies, implemented through regulatory frameworks, help limit speculative behavior, reduce contagion effects, and support sustainable growth. In Romania, the National Bank and the National Committee for Macroprudential Supervision play a key role in monitoring risks and maintaining financial stability. A stable financial system protects national resources, prevents recessions, and guarantees access to funding for both the government and the private sector. Economic risks such as cyber threats, financial market manipulation, and excessive sovereign debt pose significant challenges to national security. The 2008 crisis demonstrated the global consequences of financial instability. Effective macroprudential policies, including capital regulations and financial stress tests, help prevent crises and reduce their economic and security impact. In an era of economic volatility, implementing robust macroprudential policies is essential to safeguarding financial sovereignty and national security.